Patients’ Preferences for Androgen Deprivation Therapy in the Treatment of Intermediate-Risk Prostate Cancer - Brian De; Lisa M. Lowenstein; Kelsey L. Corrigan; Lauren M. Andring; Deborah A. Kuban; Scott B. Cantor; Robert J. Volk; Karen E. Hoffman (MDM Policy & Practice, 2022)
Background. For men with intermediate-risk prostate cancer (IRPC), adding short-term androgen deprivation therapy (ADT) to external beam radiation therapy (EBRT) has shown efficacy, but men are often reluctant to accept it because of its impact on quality of life. Methods. We conducted time tradeoffs (score of 1 = perfect health and 0 = death) and probability tradeoffs with patients aged 51 to 78 y who had received EBRT for IRPC within the past 2 y. Of 40 patients, 20 had received 6 mo of ADT and 20 had declined. Utility assessments explored 4 ADT-related side effects: hot flashes, fatigue, loss of libido/erectile dysfunction, and weight gain. Results. The most commonly reported “worst” treatment-related complication of ADT was fatigue (50% in both cohorts) followed by reduced libido/erectile dysfunction (40% in both cohorts). The utilities for fatigue were mean = 0.71 and median = 0.92 and for reduced libido/erectile dysfunction were mean = 0.81 and median = 0.92. Utilities did not differ significantly between cohorts. Assuming a 6-mo course of ADT, men reported being willing to trade 3 mo of life expectancy to avoid fatigue due to ADT and 1.8 mo to avoid sexual side effects. Patients in the ADT cohort were willing to accept the side effects of ADT in exchange for a mean 8% absolute increase in survival, whereas patients in the no ADT cohort required a 16% increase ( P  < 0.001). Conclusions. When considering treatment with ADT, men with IRPC identified fatigue and sexual dysfunction as the most bothersome side effects. Patients who declined ADT expected a larger survival benefit than those who opted for treatment. Both groups expected a survival benefit exceeding that shown by recent trials, suggesting some men may be selecting treatments inconsistent with their preferences. Highlights This study demonstrates that prostate cancer patients receiving radiation therapy are reluctant to receive androgen deprivation therapy (ADT) most commonly due to anticipated fatigue and loss of libido/erectile dysfunction. Men who had received ADT reported they would require an average 8% absolute increase in survival to tolerate its side effects, whereas those who declined ADT would require an average 16% increase. Required thresholds are well above the estimated absolute survival benefit for ADT demonstrated in recent clinical trials, suggesting an unmet need for improved patient education regarding the risks and benefits of ADT.